2022
DOI: 10.1093/gji/ggac057
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the 2017–2019 Lurestan arc seismic sequence (Zagros, Iran); complex earthquake interaction in the basement and sediments

Abstract: Summary Despite its high seismogenic potential, the details of the seismogenic processes of Zagros Simply Folded Belt (SFB) remains debated. Three large earthquakes (Mw 7.3, 5.9, and 6.3) struck in the Lurestan arc of the Zagros SFB in 2017 and 2018. The sequence was recorded by seismic stations at regional, and teleseismic distances. Coseismic surface displacements, measured by Sentinel-1A/B satellites, provide additional data and a unique opportunity to study these earthquakes in detail. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
(109 reference statements)
0
7
0
Order By: Relevance
“…Feng et al, [20] have proposed a hypocenter at 15 km depth along a basement fault that is causative for the 2017 earthquake in the Zagros region where large earthquakes have not been documented for several centuries. A coseismic source model proposed by Jamalreyhani et al, [21] suggested an oblique thrust mechanism and a fault plane with a low dip angle in the Precambrian basement. In several studies, two high slip asperities are revealed for this event with a maximum slip of about 5 to 6 m [20,[22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al, [20] have proposed a hypocenter at 15 km depth along a basement fault that is causative for the 2017 earthquake in the Zagros region where large earthquakes have not been documented for several centuries. A coseismic source model proposed by Jamalreyhani et al, [21] suggested an oblique thrust mechanism and a fault plane with a low dip angle in the Precambrian basement. In several studies, two high slip asperities are revealed for this event with a maximum slip of about 5 to 6 m [20,[22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al 21 have proposed a hypocenter at 15 km depth along a basement fault that is causative for the 2017 earthquake in the Zagros region where large earthquakes have not been documented for several centuries. A coseismic source model proposed by Jamalreyhani et al 22 suggested an oblique thrust mechanism and a fault plane with a low dip angle in the Precambrian basement. In several studies, two high slip asperities are revealed for this event with a maximum slip of about 5 to 6 m 21 , 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…The region presents one of the youngest continental collision zones on Earth and hosts frequent episodes of moderate to large shallow seismicity (e.g. Talebian and Jackson, 2004;Nissen et al, 2019;Jamalreyhani et al, 2022) (Figure 1). The Zagros changes morphology along and across strike, likely reflecting differences in the sedimentary cover -in particular its overall thickness and the spatial extents of weak, detachment-forming evaporitic layers.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of InSAR and recent improvements in seismic station coverage have allowed focused studies of major earthquake sequences that can shed light on these questions. A long-standing question in the ZFTB is the extent to which the Precambrian basement and the thick Phanerozoic sedimentary layer participate in the observed seismicity (McQuarrie, 2004;Mouthereau et al, 2007;Talebian and Jackson, 2004;Jamalreyhani et al, 2022). Nissen et al (2011) suggested a vertical separation of the seismicity in the Zagros, implying that most of the moderately-sized events (M w 5-6), especially those in the ZSFB, happen in the competent segment of the sedimentary layer and most the aftershocks in the basement, mostly triggered by stress perturbations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation